2013
DOI: 10.1155/2013/591470
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Pharmacological Properties of New Basic PLA2BrTX-I Isolated fromBothrops roedingeri(Roedinger's Lancehead) Mertens, 1942, Snake Venom

Abstract: BrTX-I, a PLA2, was purified from Bothrops roedingeri venom after only one chromatographic step using reverse-phase HPLC on μ-Bondapak C-18 column. A molecular mass of 14358.69 Da was determined by MALDI-TOF mass spectrometry. Amino acid analysis showed a high content of hydrophobic and basic amino acids as well as 14 half-cysteine residues. The total amino acid sequence was obtained using SwissProt database and showed high amino acid sequence identity with other PLA2 from snake venom. The amino acid compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
5
0
3
Order By: Relevance
“…The PhTX-II PLA 2 is an enzyme composed of a unique polypeptidic chain revealed by Tricine SDS-PAGE with molecular mass of 14,149.08 Da confirmed by mass spectrometry ( Figure 2 ). This value is similar to other isolated myotoxic PLA 2 from snake venom [ 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…The PhTX-II PLA 2 is an enzyme composed of a unique polypeptidic chain revealed by Tricine SDS-PAGE with molecular mass of 14,149.08 Da confirmed by mass spectrometry ( Figure 2 ). This value is similar to other isolated myotoxic PLA 2 from snake venom [ 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Research using a PLA 2 isolated from Bothrops roedingeri revealed high inflammatory capabilities, with a similar behavior [12] . As stated by the researcher, TNF-α, is likely to be induced by PLA 2 action, which would induce the expression of selectins resulting in release of other interleukins, such as IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 89%
“…Dominici staining made possible the identification of these as mast cells, as suspected by previous observations in sections stained with HE. Since there was no tissue damage or hemorrhage caused by PhTX-III, the source of cytokines can be explained by mast cell degranulation [12] , [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Viperid PLA 2 s show a greater limitation in maintaining their phospholipasic activity when they are submitted to variations in pH and temperature, showing maximum activity only within the narrow range of 35 and 40 C and pHs between 7.0 and 8.0 (Heleno et al, 2013;Huancahuire-Vega et al, 2014). This limitation of activity in function of temperatures and pHs near physiological levels, seems to be characteristic of group II PLA 2 s (viperid) and it is also observed that human PLA 2 s lose stability and activity outside of this range (Leidy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%